Assessment of rainfed agriculture in the Mekong Delta of Vietnam - Dang Duc Tri; Koga, Kiyoshi; Murty, V.V.N.; Loof, Rainer; The Government of Sweden (Bangkok : Asian Institute of Technology, 1992)
A study on rainfed agriculture in the Mekong Delta of Vietnam is conducted. A mathematical model for water balance analysis in paddy fields at large scale level is used. This model is refined from a model developed by AIT. The upper limit of water depth is reset, the date for starting simulation is determined by using rainfall probability, and some parameters are changed to make more suitable with t he conditions of the Mekong Delta. A computer program is also written for the refined model. In simulation model, the output will be the main factors, namely number of stress days (with the consecutive stress period is introduced) and drainage requirement. The other factors such as effective rainfall, supplementary water requirement are also provided, if needed. The simulation work has been done for four units of rainfed area in the Mekong Delta. The results obtained from simulation, considering the aforementioned factors , indicate tha t two crops per year are possible. Number of possible alternative cropping patterns are also proposed.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1992
Keywords: Water-supply, Agricultural -- Mekong Delta